Analysis of Youth Interest and Perception toward the Agribusiness Sector in the Digital Era: Analisis Minat dan Persepsi Generasi Muda terhadap Sektor Agribisnis di Era Digital - Puteri Aprilani; Putri Daulika (Agrifarm : Jurnal Ilmu Pertanian, 2025)
The agribusiness sector plays a strategic role in economic development and national food security. However, interest among the younger generation in this sector tends to decline, especially amid the rapid advancement of digital technology. This study aims to analyze the interest and perceptions of young people, particularly university students, toward the agribusiness sector in the digital era. A quantitative survey with a descriptive approach was conducted, involving respondents from various faculties within a university setting. The results indicate that although most respondents have a positive perception of agribusiness potential, their willingness to engage directly in the sector remains low. Factors such as limited understanding of digital opportunities in agribusiness, minimal exposure to modern agribusiness practices, and the dominance of industrial and service sectors in career aspirations contribute to this lack of interest. The study recommends integrating digital technology into agribusiness education and actively promoting digital-based agribusiness innovations to attract youth engagement.